Coronary Microvascular Dysfunction Assessed by Intracoronary Acetylcholine Provocation Testing Is a Frequent Cause of Ischemia and Angina in Patients With Exercise‐Induced Electrocardiographic Changes and Unobstructed Coronary Arteries. Issue 8 (9th April 2014) - Ong, Peter; Athanasiadis, Anastasios; Hill, Stephan; Schäufele, Tim; Mahrholdt, Heiko; Sechtem, Udo
ABSTRACT Background The exercise electrocardiogram (ECG) is a standard examination in patients with suspected coronary artery disease. However, despite a pathologic result, many patients undergoing diagnostic coronary angiography do not have any significant epicardial stenosis. In this study, we assessed the relation between a pathologic exercise ECG and coronary microvascular dysfunction in response to intracoronary acetylcholine (ACh) provocation in patients without any relevant epicardial stenosis. Hypothesis Coronary microvascular dysfunction is significantly more often in patients with angina, unobstructed coronary arteries and a pathologic exercise stress test compared to those without pathologic stress test. Methods This study recruited 137 consecutive patients with exertional angina pectoris who underwent diagnostic coronary angiography between September 2008 and April 2011 (68% women; mean age, 63 ± 10 years). In none of the patients was there a stenosis of >50%. All patients underwent an exercise ECG before angiography and intracoronary ACh provocation testing for assessment of coronary vasomotor responses directly after angiography. Results The exercise ECG showed an abnormal result in 69 patients (50%; ST‐segment depression ≥0.1 mV and/or reproduction of the patient's usual symptoms). The ACh test revealed a coronary vasomotor abnormality (reproduction of the patient's symptoms, ischemic ECG shifts ± diffuse distal vasoconstriction) in 87 patients (64%). Such a result was significantly more often found in patients with a pathologic exercise ECG (50/69 [72%] vs 19/69 [28%], P = 0.034). There were no other statistically significant differences between patients with and those without pathologic exercise ECG. Conclusions Coronary microvascular dysfunction is frequently found in patients with exertional angina pectoris and unobstructed coronary arteries. Such a finding is found significantly more often in presence of a pathologic exercise ECG.